2010
DOI: 10.1007/s12032-010-9660-7
|View full text |Cite
|
Sign up to set email alerts
|

Expressions of matrix metalloproteinase-7 and matrix metalloproteinase-14 associated with the activation of extracellular signal-regulated kinase1/2 in human brain gliomas of different pathological grades

Abstract: The purpose of this study is to determine whether the expressions of MMP-7 and MMP-14 are associated with the ERK 1/2 signaling pathway in human brain gliomas of different pathological grades. Immunohistochemistry and western blot methods were used to determine the expressions of MMP-7, MMP-14 and the phosphorylation status of ERK1/2 in 73 cases of human brain glioma specimens and two cases of normal brain tissues. Results indicated that the protein expression levels of MMP-7, MMP-14 and ERK1/2 phosphorylation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…[ 53 ] demonstrated that transfection of ERK1/2 siRNA led to a significant reduction of pro-MMP-7 protein production in human HT-29 colorectal adenocarcinoma cells. In concert with this finding [ 53 ], ERK1/2 activation induces MMP-7 expression in human brain gliomas [ 54 ], colon [ 55 ] and pancreatic cancer cells [ 21 , 56 ]. ERK1/2 activation could provide a source for upregulation of MMP-7 expression in human chondrosarcoma cells, but ERK1/2 activation may not be sufficient to achieve full activity of MMP-7.…”
Section: Discussionmentioning
confidence: 83%
“…[ 53 ] demonstrated that transfection of ERK1/2 siRNA led to a significant reduction of pro-MMP-7 protein production in human HT-29 colorectal adenocarcinoma cells. In concert with this finding [ 53 ], ERK1/2 activation induces MMP-7 expression in human brain gliomas [ 54 ], colon [ 55 ] and pancreatic cancer cells [ 21 , 56 ]. ERK1/2 activation could provide a source for upregulation of MMP-7 expression in human chondrosarcoma cells, but ERK1/2 activation may not be sufficient to achieve full activity of MMP-7.…”
Section: Discussionmentioning
confidence: 83%
“…Interestingly, we also noted the inverse correlation between miR-584-5p and MMP-14 levels in glioma, another common malignant tumor of the nervous system. Since MMP-14 is elevated and significantly associated with advanced grades of brain glioma, and serves as an independent prognostic factor for poor overall survival of glioma patients [46,47], we suspect that down-regulation of miR-584-5p may also contribute to high MMP-14 expression in glioma, which warrants further investigation.…”
Section: Discussionmentioning
confidence: 98%
“…Membrane type 1-Matrix Metalloproteinase (MT1-MMP, also known as MMP14) has emerged as an attractive biomarker for tumor-targeted antibody development since this protein is crucial for the progression, invasion, migration and angiogenesis of tumors[ 12 , 13 ]; and specifically, its expression correlates with tumor grade and it is associated with reduced survival in gliomas[ 14 , 15 ] and other cancers[ 16 ]. In addition, a growing body of evidence reveals that overexpression of MT1-MMP plays also a significant role in promoting gliomagenesis[ 17 ].…”
Section: Introductionmentioning
confidence: 99%